Electrosorption-Enhanced Micro-Column Solid-Phase Extraction of Traces of Cresol Red in Water Using Electrodes of Stainless Steel Wire Coated with Non-Conductive Polymer - Sui Wang; Ai-Ni Deng; Jing Wei; Zhen Guo; Ning Zhang; Zhi-Yong Guo (Adsorption Science & Technology, 2012)
A non-conductive polymer was used as an extraction matrix in electrosorption procedures. The monolithic porous polymer was prepared by the in situ stepwise polymerization of epoxy resin and diethylenetriamine as the curing agent and polyethylene glycol (PEG-1540) as the pore-forming reagent. The working electrode consisting of a metal wire coated with epoxy resin-based polymer was connected to a direct high-voltage power supply, employing a platinum wire as the counter-electrode. The aqueous solution of Cresol Red selected as a model target analyte was extracted by electrosorption-enhanced micro-column solid-phase extraction, and the concentration determined by UV–vis spectrophotometric methods. The experimental conditions, including the electric potential, the extraction and desorption time, the pH of the initial solution and ionic strength, were optimized. The results showed that the adsorption rate and capacity towards Cresol Red could be improved significantly by anodic polarization, while cathodic polarization had a smaller effect on the adsorption process. The kinetics of the process were determined as Lagergren first-order. The electrosorption isotherm was in good agreement with the Freundlich and linear equations. The equilibrium adsorption capacity was four-times higher at 300 V and 20 min, in comparison with the absence of an electric field.